Effective management of large radicular cysts using surgical enucleation vs. marsupialization – Two cases report - Fawzi RIACHI; Carine TABARANI (International Arab Journal of Dentistry (IAJD), 2010)
Radicular cysts are the most common odontogenic cystic lesions of inflammatory origin and are managed either by surgical enucleation or by marsupialization. We illustrate the possibility of complete healing of cystic periapical lesions in permanent and mixed dentition with conservation of vital structures. This article aims to report two clinical cases of radicular cysts of huge proportion treated with two different techniques in an effort to shed some light on the advantages and disadvantages as well as a brief discussion of the leading criterias that should be taken into consideration when assessing the treatment modalities.